ANALISIS INTERCARRIER INTERFERENCE (ICI) PADA OFDM-MIMO BERDASARKAN M-ARY PHASE SHIFT KEYING (M-PSK) - Arny Megasari, Ni Made; Diafari Djuni, I GAK; Ary Esta Dewi, Ni Made (Jurnal SPEKTRUM, 2019)
One of the techniques that are used to define the multipath fading it can make is Ortoghonal Frequency Division Multiplexing (OFDM). System on multicarrier technique is one that has a frequency of orthogonal to each other by using a narrow bandwidth. The weakness of the system on which occurred in mobile channel due to the technique of the time on a channel so that orthogonalitas on a subchannel would pose intercarrier interference and missing (ICI). This research aims to analyze the intercarrier interference (ICI) on the system on MIMO using BPSK and QPSK modulation in fading channel. In terms of values and graph of Bit Error Rate (BER) is proportional to the energy per Bit to noise (Eb/no). This research also aims to find out the influence of frequency on the system on-MIMO offset. The results of the comparison of the system of on-frequency offset value with MIMO that applies fruit 2, 4 and 6 kHz, a frequency of 2 kHz offset produces the most good. On the calculation of the 5 Eb N0 BPSK modulation with dB on the value of the offset frequency of 2 kHz getting the value of the Bit Error Rate 0.0037, for the value of the frequency offset 4 kHz in modulation BPSK BER 0.0058 and get value for value frequency offset of 6 kHz on modulation BPSK get the value of the BER of 0.0114.